The curative effects of dietary yeast beta-1,3/1,6-glucan on oxidative stress and apoptosis in laying quails (Coturnix coturnix japonica) exposed to lead - Seven, Ismail; Seven, Pinar Tatli; Mutlu, Seda Iflazoglu; Arkali, Gozde; Birben, Nurgul; Arslan, Aslihan Sur; Aksakal, Mesut (Tubitak Scientific & Technological Research Council Turkey, 2021)
The objective of this study was to investigate the effects of supplementation of beta-glucan to the basal diet of laying quails exposed to lead (Pb) toxicity. A total of 112 birds were randomly divided into 4 groups. The first group was fed a corn-soybean based basal diet without any supplementation (control). The second (Pb) and third (beta-glucan) groups were supplemented with 100 mg/kg of Pb (as Pb acetate) and 100 mg/kg of beta-glucan, respectively. The fourth group (Pb + beta-glucan) was fed a basal diet supplemented with 100 mg/kg of Pb and 100 mg/kg of beta-glucan. It was determined that serum total protein, albumin, and creatinine values of the Pb + beta-glucan group partially improved (P < 0.05) with the addition of beta-glucan, but globulin and blood urea nitrogen (BUN) values were similar to the Pb group (P < 0.001). Globulin and albumin/globulin ratio were not affected by the supplements. Aspartate aminotransferase (AST) ( P < 0.01) and alanine transaminase (ALT) (P < 0.001) enzyme activities in the beta-glucan and Pb + betaglucan groups were similar to the control group, unlike the Pb group. However, ALP enzyme activity was similar in all supplemented groups, unlike the control group (P < 0.01). Malondialdehyde (P < 0.001) was reduced in the liver, heart, and kidney tissues of betaglucan supplemented groups compared to the Pb group. Glutathione levels of liver and heart tissues in the Pb + beta-glucan group were significantly higher than in the Pb group (P < 0.001). Catalase and glutathione peroxidase activities were also significantly increased in all tissues by supplementation of beta-glucan as compared to the Pb group. The caspase-3 and caspase-9 protein expression levels in the liver tissue of the beta-glucan group decreased (P < 0.001) compared to the Pb group. As a result, we conclude that beta-glucan helps reduce the harmful effects of Pb toxicity in laying quails.
Keywords: Beta-glucan; lead toxicity; oxidative damage; apoptosis; quail